MOTIVASI VIETNAM MELAKUKAN KERJASAMA MILITER DENGAN AMERIKA SERIKAT DALAM MENGELOLA ANCAMAN KEAMANAN LAUT CINA SELATAN - Rahmi, Maulidina; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research that the study of diplomacy and strategy analyzes about motivation of the Vietnam military cooperation with the United States in the managing the South China Sea security threats in 2011. This research used qualitative methods which is done by explaining the case based on existing facts. The techniques used to collects data to study the case to library research in the form of journals, books, report and website. The theoretical framework applied in this research are neorealism perspective, national interest concept, nation-state analysis level, and decision making theory from Richard C. Snyder This research is motivated the Vietnam military cooperation with the United States in the managing the South China Sea security threats in 2011. The authors found that the vietnam military cooperation with the US through the MoU in 2011 was motivated by three factors. First, it aimed to increase capability navy vietnam and could bring the US Navy in the South China Sea so as to offset the naval Republic of China in the South China Sea. Second, the Memorandum of understanding is intended to safeguard the assets and economic activities of the aggressive patrols vietnam RRT in the South China Sea. Third, vietnam dare to make the Memorandum of Understanding with the United States despite being criticized China. Because, the support of the countries of Southeast Asia, namely in the form of common interests between the US, Vietnam and the countries of Southeast Asia other.Keywords: Vietnam, military cooperation, national security, South China Sea, the United States.